2010
DOI: 10.1111/j.1399-6576.2010.02335.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of accidental dural puncture and post-dural puncture headache after labour: a Nordic survey

Abstract: we found the incidence of ADP to be approximately 1%. EBP was the commonest method used for its management, and the success rate was high in most hospitals. Formal training in epidural analgesia was absent in most countries and trainees first performed it in the non-obstetric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 19 publications
3
20
0
1
Order By: Relevance
“…Some studies suggest that prophylactic EBP may reduce PDPH symptoms or need of therapeutic EBPs [14], but without evidence of efficacy [15]. The timing of EBP in the present study, with a median of 96 hours, was longer than suggested [16,17] and reported [18]. However, the optimal timing has not been established, but there are studies that suggest that EBPs performed 48 hours or later after LP could be more efficacious than early EBP [2,4,9,19].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Some studies suggest that prophylactic EBP may reduce PDPH symptoms or need of therapeutic EBPs [14], but without evidence of efficacy [15]. The timing of EBP in the present study, with a median of 96 hours, was longer than suggested [16,17] and reported [18]. However, the optimal timing has not been established, but there are studies that suggest that EBPs performed 48 hours or later after LP could be more efficacious than early EBP [2,4,9,19].…”
Section: Discussionmentioning
confidence: 81%
“…Less blood was used for EBP in OUH (median [minimum-maximum], 15 [7][8][9][10][11][12][13][14][15][16][17][18][19][20] mL) than in KUH (18 [15][16][17][18][19][20] mL) and in SCH (19 [18][19][20] mL; P = .014). The time from LP to EBP (P = .7), amount of blood used in EBP (P = .6), or duration of bed rest after EBP (P = .1) had no correlation with EBP efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…[131415161718] Zajac et al . showed that aminophylline 250 mg once daily, when administered i.v., was not effective in decreasing the incidence of PDPH in comparison to caffeine or magnesium premedication.…”
Section: Discussionmentioning
confidence: 99%
“…PDPH, described as a postural, bilateral frontaloccipital, non-throbbing pain, can arise in up to 75% of patients (Vandermeulen et al, 1994;Gleeson and Reynolds, 1998;Darvish et al, 2011). It is thought to develop because of persistent transdural leakage of cerebrospinal fluid (CSF) at a rate exceeding CSF production.…”
Section: Nerve Traumamentioning
confidence: 99%